Physical Activity and Sleep Quality of Elderly During The COVID-19 Pandemic Period - Vinanda Maria Prastica (Universitas Muhammadiyah Semarang, 2021)
COVID-19 pandemic has caused the changes on the physical activity of elderly. Physical activity can affect the sleep quality of elderly. This research aims to analyze the correlation between physical activity and quality of sleep during the COVID-19 pandemic at UPT PSTW Bondowoso. This research uses a cross sectional study design. There are 44 samples of elderlies using consecutive sampling. The instrument of this research is the characteristics of the elderly questionnaire. The elderly's physical activity instrument uses the Physical Activity Scale for Elderly (PASE) and the elderly's sleep quality uses Pitssburgh Sleep Quality Index (PSQI). The analysis of research data uses Spearman-rho (p-value <0.05). The results show that on physical activity, the median result (69.98) and good sleep quality (65.9%). The result of the correlation test shows that there is a correlation between physical activity and sleep quality (r = -0,364; p = 0,015). The conclusion of this research, is that the important of physical activity in maintaining the quality of sleep. Therefore, elderly should maintain physical activity to obtain a good sleep quality.